Required Chlorination Doses to Fulfill the Credit Value for Disinfection of Enteric Viruses in Water: A Critical Review - Rachmadi, Andri Taruna; Kitajima, Masaaki; Kato, Tsuyoshi; Kato, Hiroyuki; Okabe, Satoshi; Sano, Daisuke (Environmental science & technology, 2020)
A credit value of virus inactivation has been assigned to the disinfection step in international and domestic guidelines for wastewater reclamation and reuse. To fulfill the credit value for water disinfection, water engineers need to apply an appropriate disinfection strength, expressed as a CT value (mg × min/L), which is a product of disinfectant concentration and contact time, against enteric viruses in wastewater. In the present study, we extracted published experimental data on enteric virus inactivation using free chlorine and monochloramine and applied the Tobit analysis and simple linear regression analysis to calculate the range of CT values (mg × min/L) needed for 4-log10 inactivation. Data were selected from peer-reviewed papers containing kinetics data of virus infectivity and chlorine residual in water. Coxsackie B virus and echovirus require higher CT values (lower susceptibility) for 4-log10 inactivation than adenovirus and a human norovirus surrogate (murine norovirus) with free chlorine. On the other hand, adenovirus has lower susceptibility to monochloramine compared to murine norovirus, coxsackievirus, and echovirus. The factors that influence the required CT value are virus type, pH, water temperature, and water matrix. This systematic review demonstrates that enteroviruses and adenovirus are appropriate representative enteric viruses to evaluate water disinfection using free chlorine and monochloramine, respectively.